A neonate with multiple hand flexor tendon ruptures due to methicillin-susceptible Staphylococcus aureus sepsis: a case report - Tomomi Nakamuara; Masanori Iwai; Takeshi Inoue; Hiroki Irie; Tatsuki Karasugi; Atsuhito Seki; Masayoshi Hamaguchi; Shohei Kuraoka; Tomoyuki Mizukami; Kimitoshi Nakamura (BMC, 2023)
Abstract Background Neonatal pyogenic tenosynovitis is a highly emergent soft tissue infection. We report a case of a neonate with pyogenic tendinopathy and tendon rupture diagnosed by ultrasonography (US). He subsequently developed pyogenic arthritis and osteomyelitis during antimicrobial therapy. Case presentation A 7-day-old boy was admitted to our hospital with redness and swelling of the right index finger. US on admission showed rupture of the flexor tendon of the right index finger with inactivity. The day after admission, he developed pyogenic arthritis of the right elbow and, subsequently, pyogenic osteomyelitis. Staphylococcus aureus was identified through bacterial culture, and the patient was treated with intravenous antibiotics for 6 weeks. However, after discharge from our hospital, rupture of the flexor tendon of the left thumb was confirmed. A two-stage flexor tendinoplasty was completed at the age of 2 years and 1 month for the flexor tendon rupture on his right index finger. Conclusions In addition to blood culture, ultrasonographic evaluation should be performed in neonates with erythematous and swollen joints to identify the focus of infection as soon as possible. Moreover, repeated regular US examination is important in the follow-up of bone and soft tissue infections.